Model Pengembangan Kualitas Sumber Daya Manusia Berbasis Corporate University: Systematic Review Atas Praktik dan Peran Widyaiswara - Desta Janu Kuncoro (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Human resource quality development is a strategic element for organizational competitiveness in facing the dynamics of global competition. This study aims to develop an adaptive Corporate University-based HR development model with a primary emphasis on strengthening the strategic role of Widyaiswara as the key actor in its successful implementation. The method employed is a systematic journal review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. A systematic literature search was conducted across major academic databases for articles published between 2020 and 2025. The results indicate that Widyaiswara hold central and multifaceted roles as learning architects, transformational facilitators, as well as coaches and knowledge brokers who determine learning effectiveness and sustainability. The integration of organizational strategic plans with competency-based curricula, actively mediated by Widyaiswara, is proven to significantly enhance professional capacity and public service quality. Nonetheless, operational challenges such as resource limitations, the need for strengthening Widyaiswara capacity, and implementation gaps remain major obstacles to the maturity of this model. In conclusion, Corporate University serves as an effective strategic mechanism for improving HR competence through integrated and collaborative institutional learning functions that position Widyaiswara as organizational change agents.